2007
DOI: 10.3171/foc.2007.23.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes comparing surgical techniques for management of severe idiopathic intracranial hypertension

Abstract: Object. The object of this study was to compare surgical techniques for management of visual loss in idiopathic intracranial hypertension (IIH) unresponsive to medical treatment.Methods. The published literature was reviewed using electronic and manual search techniques. Articles were categorized based upon the surgical procedure performed, including optic nerve sheath decompression (ONSD), also called optic nerve sheath fenestration; intracranial venous sinus stent placement; ventriculoperitoneal (VP) shunt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
2
18
0
2
Order By: Relevance
“…Failure rates as high as 30% have been reported and complications are not infrequent. [50][51][52][53] Venous sinus stent placement may be an alternative treatment option for patients with IIH refractory to medical therapy. The safety and efficacy of this procedure, however, should be evaluated in a larger randomized controlled study before it is applied more widely.…”
Section: Discussionmentioning
confidence: 99%
“…Failure rates as high as 30% have been reported and complications are not infrequent. [50][51][52][53] Venous sinus stent placement may be an alternative treatment option for patients with IIH refractory to medical therapy. The safety and efficacy of this procedure, however, should be evaluated in a larger randomized controlled study before it is applied more widely.…”
Section: Discussionmentioning
confidence: 99%
“…Associating adjacent compartments surrounding the optic nerve allows local decompression of the nerve. The improvement in vision in ONSF (80%) was shown to be better compared with other methods (38.7-47%) (62). On the other hand, this method is also associated with serious complications.…”
Section: Treatmentmentioning
confidence: 83%
“…13 In our study, the twenty two patients improved gradually to be fundus free of all at four weeks post operatively. A retrospectively reviewed clinical records of eighteen patients with LPS insertion found that fourteen patients (77.8%) with preoperative headache did not complain of headache postoperatively, and four (22.2%) had headache not related to shunt function, two of the patients (11.1%) with preoperative visual complain which visual problems were reported postoperatively and thirteen patients (72.2%) did not require shunt revision so considered that LPS is effective in treatment of IIH.…”
mentioning
confidence: 92%